Education and multidisciplinary team approach in childhood diabetes - Brink, S.J.; Chiarelli, F.G. (Acta Biomedica Atenei Parmensis, 2004)
Type 1 diabetes is one of the most frequent chronic diseases in childhood. As in other chronic diseases (asthma, cystic fibrosis, rheumatoid arthritis, epilepsy) children and their families become the focus of self-treatment and the directors of their own care; thus, the health care team should be the guides who set the stage, provided advice and oversight and helped to re-focus efforts when goals were not being met all centered around the patient and family. Rather than the diabetes health care team being the only ones to initiate treatment, patient and parents have to be empowered to analyze their own data, identify patterns, problem solve with food and activity and do so based upon actual blood glucose results. Home record keeping and memory meters facilitate such analysis just as the algorithms currently in use attempt to mimic the basalbolus pattern of endogenous insulin secretion previously provided by a working pancreas. In the past, often disaster control was the modus operandi for the person with diabetes. Parents and health care providers were involved with criticism and accusations about “cheating” rather than learning how better to supervise and provide oversight. Nowadays, better knowledge of physiopathology of diabetes, availability of new insulins and devices, as well as different education of health providers pave the way for ameliorating self-care in children and adolescents with diabetes, with the aim of improving metabolic control and quality of life of children and their family, with the ultimate aim of preventing macrovascular and microvascular complications.